Nutrient retention and availability of biochars prepared by co-pyrolysis of vinasse with sugarcane filter cake - Suwanree, Siraprapra; Knijnenburg, Jesper T. N.; Olcer, Emirhan M.; Jetsrisuparb, Kaewta (CHULALONGKORN UNIV, METALLURGY & MATERIALS SCIENCE RESEARCH INST, 2024)
The disposal of vinasse, a nutrient-rich by-product of ethanol production, is challenging because of the low pH and emissions of harmful gases and smells. Here, biochars were produced by pyrolysis of mixtures of filter cake and vinasse (0.25 w/v to 1 w/v) at 550 degrees C. The effects of filter cake to vinasse ratios on the biochar yield, pH, ash content, total nutrient (P, K, Ca, and Mg) content, and nutrient availability were investigated. Increasing the filter cake to vinasse ratio increased the biochar yield and ash content and lowered the biochar pH from 10.3 for 0.25-BC to 8.2 for filter cake biochar (FC-BC). Lower filter cake to vinasse ratios increased the total K content from 7.9 g center dot kg-1 for FC-BC to 75.9 for 0.25-BC. Nutrient recovery in the biochars was high (79.5% to 130.2%). Whereas P, Ca, and Mg extractability in water was 50%). These results highlight the potential suitability for use in agricultural applications. Conversion of vinasse into value-added biochar could reduce waste treatment cost and improve soil health.
Keywords: Thermal treatment; Agricultural waste; Biochar; Sugarcane; Soil fertilizer; PHOSPHORUS; RELEASE; SPECIATION; BAGASSE; Materials Science